2007
DOI: 10.1111/j.1365-2567.2007.02594.x
|View full text |Cite
|
Sign up to set email alerts
|

Triacylated lipoproteins derived from Mycoplasma pneumoniae activate nuclear factor‐κB through toll‐like receptors 1 and 2

Abstract: Triacylated lipoproteins derived from Mycoplasma pneumoniae activate nuclear factor-jB through toll-like receptors 1 and 2 IntroductionMycoplasmas are wall-less parasitic bacteria, and the smallest organisms capable of self-replication.1 Mycoplasma pneumoniae causes primary atypical pneumonia, tracheobronchitis and pharyngitis in humans.2 However, virulence factors such as endotoxins and exotoxins, which cause such diseases, have not been identified in M. pneumoniae. Adherence of invading mycoplasma to the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 47 publications
4
79
0
Order By: Relevance
“…Therefore, lipoproteins, which are ligands for TLR2, are possible candidates for an inflammation-inducing factor in M. genitalium. In fact, we previously demonstrated that lipoproteins derived from M. pneumoniae induce NF-〉 through TLR2 (41,44). To elucidate whether M. genitalium induces NF-B through TLR2, we initially performed TX-114 phase partitioning of M. genitalium.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, lipoproteins, which are ligands for TLR2, are possible candidates for an inflammation-inducing factor in M. genitalium. In fact, we previously demonstrated that lipoproteins derived from M. pneumoniae induce NF-〉 through TLR2 (41,44). To elucidate whether M. genitalium induces NF-B through TLR2, we initially performed TX-114 phase partitioning of M. genitalium.…”
Section: Resultsmentioning
confidence: 99%
“…The others were predicted to be lipoproteins MPN611 and MPN162 and designated NF-Bactivating lipoprotein 1 (N-ALP1) and N-ALP2, respectively. N-ALP1 and N-ALP2 activated TLR signaling through TLR1 and TLR2, indicating that both are triacylated lipoproteins (9). Because mycoplasmas lack cell walls, they do not contain known pathogen-associated molecular patterns (PAMPS) such as those corresponding to lipopolysaccharide (LPS), peptidoglycan (PGN), or lipoteichoic acid.…”
mentioning
confidence: 99%
“…Such LAMPs are a subunit of the F 0 F 1 -type ATPase and are diacylated [144]. In addition other triacylated lipoproteins signal through TLR 1 and 2 but are independent of TLR6 [145]. As expected by these data, an in vivo model of pulmonary mycoplasma infection is heavily reliant on TLR2 [146].…”
Section: Cell Wall Free Bacteriamentioning
confidence: 58%